Asymmetry in antlers of barren-ground caribou, Northwest Territories, Canada - Miller, Frank L. (Rangifer, 1986)
Pairs of antlers were obtained from 287 barren-ground caribou (Rangifer tarandus groenlandicus) of the Kaminuriak herd in the Northwest Territories, Canada. The morphological dominance of the brow tines by antler pair was determined: 15.7% were enlarged on the left; 14.6% on the right; 14.6% on both sides; and 55.1% on neither side. No evidence for a greater rate of occurrence of left or right dominance of the brow tine was obtained when considered by sex or age class (P >0.05). Antler pairs with both brow and bez tines present varied from 84.4% for males with their 5th to 10th set of antlers; 39.3% for males with their 2nd to 4th set; 21.2% for females with their 5th to 16th set; and 6.3% for females with their 1st to 4th set. Both brow and bez tines were present proportionately more often than expected on antler pairs from males compared to females regardless of age (P <0.005). Both brow and bez tines also were present proportionately more often than expected on antler pairs from males (P <0.005), females (P <0.01), or both sexes combined (P <0.01) with their 5th or later set than compared to when they had their 4th or earlier set.